2003
DOI: 10.1111/1468-2508.00217
|View full text |Cite
|
Sign up to set email alerts
|

Voided Ballots in the 1996 Presidential Election: A County-Level Analysis

Abstract: This county-level study examines factors associated with the rate of voided presidential ballots in the 1996 elections. Evidence indicates that voided ballots are significantly more prevalent in counties with higher percentages of African Americans and Hispanics. The relationship between voided ballots and African Americans disappears, however, in counties using voting equipment that can be programmed to eliminate overvoting. The rate of voided ballots is lower in larger counties and in counties with a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
87
2
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(94 citation statements)
references
References 19 publications
1
87
2
4
Order By: Relevance
“…Media organizations contributed their own evidence: using data the National Opinion Research Center collected on 175,010 Florida ballots that did not register a valid vote for president, they concluded that rejected ballots were more common in heavily black precincts than in heavily white ones (Fessenden 2001;Keating and Mintz 2001). Multi-state investigations detected a similar relationship between blacks and uncounted votes (Brady et al 2001, 26, 40;GAO 2001;HCGR 2001;Knack and Kropf 2001).…”
Section: A Black-white Gap In Voided Ballots Existsmentioning
confidence: 83%
See 2 more Smart Citations
“…Media organizations contributed their own evidence: using data the National Opinion Research Center collected on 175,010 Florida ballots that did not register a valid vote for president, they concluded that rejected ballots were more common in heavily black precincts than in heavily white ones (Fessenden 2001;Keating and Mintz 2001). Multi-state investigations detected a similar relationship between blacks and uncounted votes (Brady et al 2001, 26, 40;GAO 2001;HCGR 2001;Knack and Kropf 2001).…”
Section: A Black-white Gap In Voided Ballots Existsmentioning
confidence: 83%
“…In Florida, for example, the NAACP sponsored a massive drive that brought many African Americans to the polls for the first time, perhaps contributing to the black-white gap. Research on the link between inexperience and invalidation has yielded mixed results, however (Holt and Berens 2001;Jewett 2001;Klinkner 2001;Knack and Kropf 2001). Finally, some add that blacks may be less likely than whites to seek or receive assistance in using machines and correcting mistakes, especially where there is racial intimidation or a history of disenfranchisement (e.g., USCCR 2001).…”
Section: A Black-white Gap In Voided Ballots Existsmentioning
confidence: 99%
See 1 more Smart Citation
“…Optical-scanners were in place when the IRV reform passed, and these ballots were designed to fit that system. Generally, the optical-scan method has been shown to produce moderate Hood 2002, Knack andKropf 2003;Sinclair and Alvarez 2004) to relatively low rates of uncounted votes (Ansolabehere and Stewart 2005;Kimball, Owens, and Keeney 2004).…”
Section: Instant-runoff Voting San Francisco Stylementioning
confidence: 99%
“…However, because those differences were rare in the earlier IRV analysis (Neely and Cook 2008) we expect there to be no significant difference in overvotes between areas with more male or female residents. Other factors have been shown to matter in the rate at which voters cast uncounted ballots: elderly voters (Darcy and Schneider 1989;Kimball and Kropf 2005;Stiefbold 1965), less educated voters (Walker 1966;Bullock and Hood 2002), and poorer voters (Darcy and Schneider 1989;Kimball, Owens, and Keeney 2004;Knack and Kropf 2003) have been identified as more likely to cast a ballot that is not counted. However, the prior IRV study found few of these relationships.…”
Section: Literature and Hypothesesmentioning
confidence: 99%